2021
DOI: 10.1182/bloodadvances.2020002440
|View full text |Cite
|
Sign up to set email alerts
|

FcεRIγ-negative NK cells persist in vivo and enhance efficacy of therapeutic monoclonal antibodies in multiple myeloma

Abstract: Monoclonal antibodies (mAbs) are a central component of therapy for hematologic malignancies. Widely used mAb agents in multiple myeloma (MM) include daratumumab and elotuzumab. However, not all patients respond to these agents, and resistance is a significant clinical issue. A recently discovered subset of human natural killer (NK) cells lacking expression of FcεRIγ (g-NK cells) was found to have a multifold increase in antibody-dependent effector functions after CD16 crosslinking. In this study, we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…Although these cells express a lower amount of natural cytotoxic receptors and thus show weak responsiveness toward the K562 tumor cell line compared to FcϵRIg+ NK cells (74), they display an increased activity through Ab-dependent stimulation (74) and ADCC (75). Recently, a method to ex vivo expand these so-called "g-NK" cells has been published (77). Although the expansion is only possible from previously HCMVinfected donors, the resulting cells possess some interesting features.…”
Section: Making Highly Active Natural Killer Cells For Therapymentioning
confidence: 99%
“…Although these cells express a lower amount of natural cytotoxic receptors and thus show weak responsiveness toward the K562 tumor cell line compared to FcϵRIg+ NK cells (74), they display an increased activity through Ab-dependent stimulation (74) and ADCC (75). Recently, a method to ex vivo expand these so-called "g-NK" cells has been published (77). Although the expansion is only possible from previously HCMVinfected donors, the resulting cells possess some interesting features.…”
Section: Making Highly Active Natural Killer Cells For Therapymentioning
confidence: 99%
“…The common gamma chain (γc) receptor family cytokines, including IL-2, IL-15, and IL-21, are required for the generation, persistence, and homeostasis of adaptive NK cells ( 57 ). IL-2 was first discovered as a T cell growth factor in 1976 and was later found to have various pleiotropic properties, including the ability to augment the cytolytic activities of NK cells and cytotoxic T cells.…”
Section: Functional Characteristics Of Adaptive Nk Cellsmentioning
confidence: 99%
“…Moreover, 5 of the 7 mice eliminated the burden of myeloma, with a survival rate of up to 100% after 60 days. Interestingly, the persistence of expanded g - NK cells is detected in the blood, spleen and, BM relative to that of c-NK cells in the MM model ( 57 ).…”
Section: Clinical Relevance Of Adaptive Nk Cellsmentioning
confidence: 99%
“…Equally, FcεRIγ-deficient NK (g-NK) cells are a rare group of cells originated from CMV-seropositive subjects (CD38low and SLAMF7low). An experimentation demonstrated that with respect to traditional NK cells, ex vivo g-NK cells, in combined administration with daratumumab, presented an augmented cytotoxicity against MM cells [ 152 ].…”
Section: Acute Leukemiamentioning
confidence: 99%